Water, life, and profit : fluid economies and cultures of Niamey, Niger - Keough, Sara Beth, 1976-; Youngstedt, Scott M. (New York : Berghahn Books, 2019)
"Water, Life, and Profit offers a holistic analysis of the people, economies, cultural symbolism, and material culture involved in the management, production, distribution, and consumption of drinking water in the urban context of Niamey, Niger. Paying particular attention to two key groups of people who provide water to most of Niamey's residents - door-to-door water vendors, and those that sell water in one-half liter plastic bags (sachets) on the street or in small shops -, the authors offer new insights into how Niamey's water economies affect gender, ethnicity, class, and spatial structure today"--Provided by publisher.
Introduction. Why water? Why now? -- Situating water in the 21st century -- Historical urban development in Niamey -- Accessing water in Niamey -- Water delivery vendors in Niamey -- "Pure water" in Niamey -- Fluid materialism in Niamey -- Conclusion.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Drinking water -- Niger -- Niamey; Drinking water -- Economic aspects -- Niger -- Niamey; Drinking water -- Social aspects -- Niger -- Niamey; Bottled water industry -- Economic aspects -- Niger -- Niamey; Bottled water industry -- Social aspects -- Niger -- Niamey; Eau potable -- Niger -- Niamey; Eau potable -- Aspect économique -- Niger -- Niamey; Eau potable -- Aspect social -- Niger -- Niamey; Eau en bouteille -- Industrie -- Aspect économique -- Niger -- Niamey; Eau en bouteille -- Industrie -- Aspect social -- Niger -- Niamey; SOCIAL SCIENCE / Anthropology / Cultural & Social; SOCIAL SCIENCE / Anthropology / Cultural; Drinking water; Drinking water -- Economic aspects; Niger -- Niamey; Drinking Water; Water Distribution; Water Economy; Water Vendors; West Africa